Assessing The Contribution of The People’s Education Program (Prodira) Policy Toward Senior High School Education Performance in Gorontalo Province - arwildayanto arwildayanto arwildayanto (Magister Ilmu Administrasi Publik, 2018)
The purpose of the study is to assess the effectiveness of people’s education program (PRODIRA).The study used a mixed research methods approach with concurrently embedded, combinationmodel of the qualitative and quantitative methods. The data were collected using interview,documentation and observation techniques from respondents who included headmasters, teachers,exchequers, students’ parents and school committee members in senior high schools, vocationaland Islamic senior high schools (SMA/SMK/MA) in Gorontalo Province. The results indicated thatthe implementation of PRODIRA program by the Provincial Government of Gorontalo has beeneffective in enhancing quality of performance of Senior High School Education (SLTA ) in GorontaloProvince as reflected in the increase of knowledge index, increased availability of SMA/SMK/MAinstitutions, percentage of schools that are categorized as being in good condition and a declinein school dropout rates.